Contribuições da abordagem “design orientado aos dilemas” na construção de soluções para o bem-estar no contexto da maternidade nas empresas - Araújo, Luciana Cattony Silva (Universidade do Vale do Rio dos Sinos, 2021)
Studies show that motherhood is one of the main barriers for women to advance their careers within companies. From the dilemma “playing motherhood versus participating in the labor market”, and the potential of Dilemma-Driven Design (dilemma-driven design) for the development of solutions that reduce negative emotions and promote positive emotions, comes to the problem of this research: How the Dilemma Oriented Design can contribute to the well-being of mothers, considering the other actors involved in the context of motherhood in companies? To answer this problem, an empirical practice was proposed, divided into three stages, within the same organizational context. The first stage was a focus group with mothers and pregnant women to understand the main dilemmas experienced from the perspective of working mothers. In the second stage, in-depth interviews with leaders and human resources professionals, with and without children, were carried out as a way to understand the theme from the perspective of other actors who are part of the context of motherhood in companies. And finally, in the third stage, a workshop was held with specialists and mothers to co-create solutions to minimize the dilemmas encountered. Regarding the results, it was possible to identify that the dilemmaoriented design has a strong contribution to the delimitation of the design problem; being a strong resource for generating empathy, connecting people intensely to the project, which is advantageous, especially when dealing with complex problems.
Keywords: Maternidade; Carreira; Dilemas; Design orientado ao dilema; Design estratégico; Motherhood; Career; Dilemmas; Dilemma-driven-design; Strategic design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial